Pertumbuhan Penjualan, Ukuran Perusahaan, Leverage, Modal Kerja, Likuiditas, Perputaran Kas dan Pengaruhnya Terhadap Profitabilitas Pada Industri Makanan dan Minuman yang Listing Di Bursa Efek Indonesia (BEI) - Stefannie Halim; Felicia Felicia; Valencia Lius; Tiffany Veronica; Bayu Wulandari (Ekonomis: Journal of Economics and Business, 2021)
This study was made with the aim of testing whether sales growth, company size, leverage, working capital, liquidity, cash turnover have an influence on profitability in manufacturing companies in food and beverage sub-sector for 2017-2019 period.Quantitative methods are used in this analysis. The use of purposive sampling technique leaves 13 (thirteen) companies from the research population as many as 26 (twenty six) companies listed on the Indonesia Stock Exchange (IDX). A total of 39 (thirty nine). The source of the data for this research comes from the financial statements of companies published on www.idx.co.id. The research method used is descriptive analysis method and multiple linear regression analysis method. The dependent variabel in this study is profitability, while the independent variabel are sales growth, company size, leverage,liquidity, and cash turnover.The results obtained in this study are partially sales growth, working capital turnover have a significant effect on profitability, while company size, leverage, liquidity, and cash turnover have no significant effect on profitaibility. The findings of this study suggest that manufacturing companies in food and beverage sub-sector need to pay attention to sales growth and working capital turnover.